Predictors of complementary feeding practices among children aged 6-23 months in five countries in the Middle East and North Africa region - Linda Shaker‐Berbari; Vilma Qahoush Tyler; Chaza Akik; Zeina Jamaluddine; Hala Ghattas (Wiley, 2021)
Abstract Ensuring diets of children aged 6-23 months meet recommended guidance is crucial for growth and development and for the prevention of malnutrition including stunting, wasting and micronutrient deficiencies. Despite some improvement, indicators related to undernutrition and overnutrition fall short of global targets in the Middle East and North Africa (MENA) region that consist of low‐ and middle‐income countries witnessing political and social changes and a nutrition transition. This research aims at reviewing the situation related to the diets of children aged 6-23 months in five selected countries in the MENA region, examining factors affecting complementary feeding and providing recommendations for guiding effective strategies to improve it. The study triangulated data on complementary feeding status and predictors from semistructured interviews with 30 key informants, and multivariable analysis of household surveys in Egypt, Jordan, Lebanon, State of Palestine and Sudan including data on refugees in Lebanon and Jordan. There remain considerable gaps in complementary feeding differing noticeably among geographic areas. Findings from qualitative and quantitative analyses showed that maternal factors, including maternal education and age, household level factors such as paternal education and wealth, community‐level factors (culture and geographic location), and utilization of health services, were associated with minimum dietary diversity (MDD), minimum meal frequency (MMF) and minimum acceptable diet (MAD) at varied levels in the five countries. Interventions to improve complementary feeding practices should include actions tailored to the needs of the population at multiple levels including at the caregiver's level, household, service use, community and policy level.